Digital Trust and Transparency: Employee Perception of the Honesty of Attendance Data Through Hris at PT Sitoy Leather Products Indonesia (Kendal) - Eti Aisah; Sherli Junianingrum; Abdul Khafid (Sean Institute, 2026)
This study aims to explore employees’ perceptions of transparency, accuracy, and fairness in the Human Resource Information System (HRIS) used for attendance recording at PT Sitoy Leather Products Indonesia. Employing a qualitative phenomenological approach, this research investigates employees’ lived experiences through in-depth interviews, observation of daily attendance processes, and review of supporting documents. The findings reveal that most employees perceive HRIS as improving attendance accuracy, reducing manual errors, and accelerating the correction process. The system is considered transparent when employees can access their attendance history and when correction procedures are handled openly and responsively. However, several challenges persist, including delayed data synchronization, biometric misreads, and variations in digital literacy among employees. Communication from the HR department also plays a critical role in shaping employee trust. Overall, HRIS contributes positively to enhancing trust, accountability, and efficiency in attendance management within a manufacturing environment.